True Digital Control : Statistical Modelling and Non-Minimal State Space Design. - Taylor, C. James (Wiley, 2013)
True Digital Control: Statistical Modelling and Non-Minimal State Space Designdevelops a true digital control design philosophy that encompasses data-based model identification, through to control algorithm design, robustness evaluation and implementation. With a heritage from both classical and modern control system synthesis, this book is supported by detailed practical examples based on the authors' research into environmental, mechatronic and robotic systems. Treatment of both statistical modelling and control design under one cover is unusual and highlights the important.